Cardiac effects of drugs used for induction of labour and prevention and treatment of postpartum haemorrhage - Lee, Sindy; Cauldwell, Matthew; Wendler, Renate (International journal of cardiology congenital heart disease, 2021)
Pregnancy presents significant stresses to a woman's body from the physiological changes to the cardiovascular system, fluid shifts at the time of delivery and the risk of major haemorrhage in the peri-partum period. Medications used routinely in daily obstetric practice may have potent vasoactive effects. While most parturients are considered to be healthy and can withstand these significant physiological challenges, as the prevalence of cardiac disease among pregnant women increases it is important to consider the additional impact these medications may have in order to minimise the risk of cardiovascular instability and decompensation. This article will review drugs used in the induction of labour and the management of post-partum haemorrhage, and their relevance for women with cardiac disease.